THE EFFECTIVENESS OF SOCRATIVE APPLICATION FOR FORMATIVE ASSESSMENT IN TEACHING VOCABULARY AT SMA MUHAMMADIYAH 1 PONOROGO - Nurhasanah, Fitriani; Khasanah, Nurul (ELTALL: English Language Teaching, Applied Linguistic and Literature, 2020)
The objective of this research was to find out whether there is any significant difference vocabulary mastery between students who used socrative application for formative assessment and who are not used socrative application for formative assessment. This research applied quantitative research approach and used quasi-experimental design. In this research, the researcher used two classes (experimental class and control class) as a sample. The population of eleventh science grade in SMA Muhammadiyah 1 Ponorogo was 115 students. The number of sample in this research was 30 students of experimental class (XI IPA4) and 31 students of control class (XI IPA3). The researcher used simple random sampling to choose the sample in this research. The data were obtained by using a pre-test and post-test. The pre-test was given to both classes before the treatment and the post-test was given after the treatment. After getting the score of pre-test and post-test, the data were analyzed and processed by using T-test formula using SPSS 23 versions for Windows. The result of this research showed that the average of post-test of experimental class is 87.70 and the average score of post-test of control class is 77.74. The value of t-test = 3,226 with df = 59 on level significance 5%. According to the table value “t” = 1,671. Then tcount  higher than ttable (3,226 > 1,671). Therefore, H1 is accepted and H0 is rejected. So, it can be concluded that there is significant difference on students’ vocabulary mastery that used socrative application for formative assessment and that are not. In the other words, Socrative Application is effective for formative assessment on students’ vocabulary mastery of eleventh science grade of SMA Muhammadiyah 1 Ponorogo.